Business research methods - Zikmund, William G.; Babin, Barry J.; Carr, Jon C.; Griffin, Mitch (South-Western Cengage Learning, 2013)
Its student-friendly design contains numerous examples illustrating real-world research in management, marketing, finance, accounting, and other business areas.